The Role of Teachers in Facing the Challenges of Beginning Mathematics - Arvin Efriani; Zulkardi Zulkardi; Ratu Ilma Indra Putri; Nyimas Aisyah (Pusat Penerbitan Universitas (P2U) Unisba, 2020)
This study aims to describe the role of teachers in facing the challenges of early mathematics learning in early childhood so that can be one of the teacher's reference sources in teaching beginning mathematics. This research is a literature study through the stages of problem formulation, literature searching, data evaluation, analysis, and interpretation. The analysis technique that is used is descriptive analysis. For finding out the role of teachers, teachers should first pay attention to the principles of early childhood learning by considering the characteristics of early childhood. The teacher's role can be concluded from this article through three stages, namely the role of the teacher in planning, the role of the teacher in implementation, and the role of the teacher in evaluating. At the planning stage, the teacher prepares a learning tool that is adjusted to the child's characteristics and learning principles. At the implementation stage, the teacher is a facilitator. Whereas at the evaluation stage, the teacher reviews the material that has been given by the child with the planned tool can be in the form of making a community and workshop to share and find solutions to problems. Keywords: Early Mathematics, Early Childhood, The Role of The Teacher Abstrak Penelitian ini bertujuan untuk mendeskripsikan peran guru dalam menghadapi tantangan pembelajaran matematika permulaan pada anak usia dini sehingga dapat menjadi salah satu sumber acuan guru dalam mengajarkan matematika permulaan. Penelitian ini merupakan studi literatur melalui tahap formulasi masalah, pencarian literatur, evaluasi data, analisis, dan interpretasi. Teknik analisis yang digunakan yaitu analisis deskriptif. Untuk mengetahui peran guru, sebaiknya guru terlebih dahulu memperhatikan prinsip pembelajaran anak usia dini dengam mempertimbangkan karakteristik anak usia dini. Adapun peran guru yang dapat disimpulkan dari artikel ini melalui tiga tahapan yaitu peran guru dalam perencanaan, peran guru dalam pelaksanaan, dan peran guru dalam mengevaluasi. Pada tahap perencanaan guru mempersiapkan perangkat pembelajaran yang disesuaikan dengan karakteristik anak dan prinsip pembelajaran. Pada tahap pelaksanaan guru sebagai fasilitator. Sedangkan pada tahap evaluasi guru mengulas materi yang sudah diberikan anak dengan perangkat yang telah direncanakan dapat berupa membuat komunitas dan lokakarya untuk saling berbagi dan menemukan solusi dari permasalahan. Kata Kunci: Matematika Permulaan, Anak Usia Dini, Peran Guru.